SYNTACTICAL FEATURES OF POLYMODALITY IN ADVERTISING - Omonova Makhfurat Keldiyarovna (Bright Mind Publishing, 2025)
Advertising is a complex field where the integration of multiple modes of communication—referred to as polymodality—has become a standard practice. Polymodality refers to the use of various communicative modes, such as text, visuals, audio, and interactive elements, to deliver a cohesive message. Advertisers strategically utilize these different modes to reinforce their message, persuade the audience, and create memorable experiences. This article delves into the syntactical features of polymodal advertisements, analyzing how these elements are structured and interact to convey meaning effectively.
Keywords: Advertise, polymodality, to convey meaning, Textual Structure, Visual Syntax, Auditory Syntax, Interactive Syntax, audio components, to contribute, visual elements, textual elements, Gestural and spatial elements.